Teachers’ responses to Interactive Whiteboard (IWB) adoption in a secondary vocational School in Ningbo, China - Yu, Cheng (2020)
This thesis explores factors affecting teachers’ utilization of Interactive Whiteboards (IWBs) in their teaching in a secondary vocational school in Ningbo, where they had been introduced into all classrooms as part of a local government sponsored project.